Does progressivity always lead to progress? The impact of local redistribution on tax manipulation - Tommaso Giommoni (Center for Economic Studies and ifo Institute (CESifo), 2019)
The goal of this paper is to study the effects of introducing income redistribution at the municipal level, with the adoption of local tax progressivity. In particular, we analyse whether this complex fiscal tool modifies the incentives of local politicians to be strategic leading to higher tax manipulation, in the form of political budget cycle. We exploit an Italian reform of the local personal income tax (PIT), which was flat before the intervention, that allows mayors to introduce progressive schemes. First, we make use of the staggered timing of local elections to estimate a Difference-in-Differences model and we find that the reform consistently amplifies political budget cycle of local PIT. In terms of mechanism, progressivity allows mayors to target diverse income groups and to play different strategies: high income rates, indeed, are subject to larger manipulation than the moderate ones. Second, we exploit the fact that income concentration level is a valid predictor for the introduction of progressivity. The main results are confirmed in a Triple-Differences analysis. And finally, we show that manipulation is rewarding from an electoral point of view. These results reveal a negative side of decentralizing income redistribution as it may lead to consistent tax manipulation and large distortions in fiscal policy.
Keywords: D72; E62; H71; P16; 330; tax progressivity; personal income tax; political budget cycle; tax manipulation; fiscal federalism